Strain dependent differences between rodents in nicotine-induced locomotor sensitization - Kayır, Hakan; Uzbay, I. Tayfun (Journal of Dependence, 2001)
Object: In the present study, strain dependent differences between mice and rats were investigated in the acute locomotor (LM) effect of nicotine, and LM sensitization produced by repeated administration of nicotine. Method: Adult male Swiss-Webster mice and Wistar rats were subjects. Nicotine (1 mg/kg) or saline (control group) were injected to mice or rats intraperitoneally, and LM activities were recorded immediately by intervals of 5 min for total 30 min. Nicotine and saline injections were lasted once a day for 5 days repeatedly. Results: Nicotine (1 mg/kg) had no significant effect on total LM activity (30 min) of both mice and rats at the first injection. When the data were analyzed by 5 min intervals, a significant increase in LM activity was only determined in rats treated with nicotine. On the 5th day, only the LM activity (30 min) of nicotine treated rats was increased significantly compared to both control (saline treated) group and the 1st day of the same group. That increase was also significant in 5 min intervals of LM activity. Discussion: Nicotine administration to mice and rats by the same protocol resulted in sensitization only in rats. Results showed that sensitization development to nicotine in rodents has strain dependent variations.